Identifikasi Keberadaan Batu Apung Berdasarkan Data Georadar dan Data Geolistrik Resistivitas di Kecamatan Ampenan dan Kecamatan Sekarbela, Kota Mataram - Arsi, Sefti Dini; Farid, Muhammad; Refrizon, Refrizon (Jurusan Fisika FMIPA Universitas Andalas, 2025)
Retraction Notice This article has been retracted at the request of the Editor-in-Chief after reviewing the available evidence and verifying the report received. The article entitled “Identification of the Presence of Pumice Stone Based on Georadar Data and Geoelectric Resistivity Data in Ampenan District and Sekarbela District, Mataram City” published in Jurnal Ilmu Fisika, Vol. 17 No. 1 (March 2025), was found to have a similarity level of approximately 94% with another article previously published in Lambda: Jurnal Pendidikan MIPA dan Aplikasinya, Vol. 5 No. 1 (April 2025), titled “Kombinasi Metode Georadar dan Geolistrik Resistivitas untuk Mendeteksi Keberadaan Batu Apung di Kota Mataram.” The research data (Georadar and Geoelectric data) belong to Universitas Mataram and were used without permission from the data owner. Therefore, Arsi et al., as the authors of the article published in Jurnal Ilmu Fisika, are considered to have published the article without authorization from the rightful data owner. As a result, this article has been formally retracted from the Jurnal Ilmu Fisika archive.